2021
DOI: 10.1038/s41598-021-94942-7
|View full text |Cite
|
Sign up to set email alerts
|

Multiple climate change-driven tipping points for coastal systems

Abstract: As the climate evolves over the next century, the interaction of accelerating sea level rise (SLR) and storms, combined with confining development and infrastructure, will place greater stresses on physical, ecological, and human systems along the ocean-land margin. Many of these valued coastal systems could reach “tipping points,” at which hazard exposure substantially increases and threatens the present-day form, function, and viability of communities, infrastructure, and ecosystems. Determining the timing a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 93 publications
0
16
0
3
Order By: Relevance
“…Estimated trends and modelled sea level rise (between 0.9 and 1.8 m) have shown that 4.2-13.1 million US citizens could be at risk of inundation (Hauer et al, 2016). Recent assessments (Barnard et al, 2019(Barnard et al, , 2021 suggest that many coastal regions could be reaching a 'tipping point' with regard to coastal flooding hazard, biodiversity, and ecosystem function if current trends in sea level rise hold constant or accelerate and steps to mitigate these trends are not taken.…”
mentioning
confidence: 99%
“…Estimated trends and modelled sea level rise (between 0.9 and 1.8 m) have shown that 4.2-13.1 million US citizens could be at risk of inundation (Hauer et al, 2016). Recent assessments (Barnard et al, 2019(Barnard et al, , 2021 suggest that many coastal regions could be reaching a 'tipping point' with regard to coastal flooding hazard, biodiversity, and ecosystem function if current trends in sea level rise hold constant or accelerate and steps to mitigate these trends are not taken.…”
mentioning
confidence: 99%
“…Therefore, the urban growth-climate change-flood risk nexus in these urban hubs must be managed. Also, since most urban development occurs along coasts in the Arabian Gulf, climate change puts these hubs at additional risk of rising sea levels 1 , 36 . Hence, unless wise and proactive flood and sea-level rise mitigation and adaptation actions are taken, the environmental cost of urban growth and climate change will exacerbate, and tipping points may be reached in the region’s physical systems.…”
Section: Discussionmentioning
confidence: 99%
“…The imagery is from North and South Carolina taken after Hurricane Florence (2018). Post storm imagery can be used to monitor the effects of hurricanes on coastal communities (Chen et al., 2018) and ecosystems (Barnard et al., 2021) and coastal change (Goldstein et al., 2020). The images are labeled using the following classes: (a) water, (b) sand, (c) vegetated surface, and (d) development.…”
Section: Datasets and Case Studiesmentioning
confidence: 99%